The Effect of Rice Hull in Diets on Performance, Antioxidant Capacity and Blood Chemical Profile of Bali Duck - Partama , I.B. Gaga; Yadnya, T.G. Belawa; Bidura, I.G.N.G.; Trisnadewi, A.A.A. Sri; Yupardhi, W. Sayang (International Journal of Poultry Science, 2019)
Background and Objective: An experiment was conducted to study the effects of diets with rice hull urea deammoniated and biofermented by a complex of lactobacillus bacteria with Piper betle L. leaf supplement on the performance, antioxidant capacity and blood chemical profile of male Bali ducks in the growth phase. Methodology: The experiment was a completely randomized design (CRD) with five treatments; the treatments were: (A) control treatment, (B) diet containing 10% rice hull, (c) a diet containing 10% ammoniated and biofermented rice hull, (D) a diet containing 10% rice hull and Piper betle leaf and (E) a diet containing 10% ammoniated and biofermented rice hull and Piper betle leaf. Each treatment consisted of five Bali ducks and each treatment was replicated four times. Observed variables were consumption and digestibility of diets, final body weight, body weight gain and feed conversion ratio (FCR). Results: The results showed that diets containing 10% rice hull ammoniated and biofermented did not affect feed consumption (p>0.05), although feed digestibility and final body weight increased (p<0.05). However, in these diets, decreases were observed in the levels of total body cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL) and triglyceride (TGA) as well as the levels of sugar and uric acid, whereas weight gain and FCR were not significantly affected (p>0.05). Diets containing rice hull deammoniated and biofermented with piper betel leaf supplement decreased concentrations in Bali duck blood. Conclusion: In conclusion, diets offered with rice hull urea deammoniated and biofermented supplemented with Piper betle leaf improved the performance, antioxidant capacity and blood chemical profile of Bali ducks in the growth phase.